Penguatan Kompetensi Manajemen Media Digital dalam Meningkatkan Kreativitas Siswa SMKN 10 Bandung - Mugi Puspita; Indarta Priyana; Aggi Panigoro; Agung Pramayuda (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aimed to improve the understanding and skills of students at SMKN 10 Bandung in managing digital media creatively and productively as part of strengthening vocational competencies in the fields of creative industries and digital communication. The activity was conducted on May 26, 2026, at SMKN 10 Bandung, targeting students who required reinforcement in digital literacy, content planning, personal branding, and the use of digital media to support creativity and readiness to enter the digital work ecosystem. The implementation method used a participatory training approach consisting of interactive lectures, discussions, content idea mapping, simple content concept development practices, and collective reflection. The training materials covered the functions of digital media, content management strategies, digital media ethics, audience recognition, and the use of digital media as a space for expression, portfolio development, and collaboration. The results showed that students were able to understand the role of digital media not only as a means of entertainment but also as a productive medium for showcasing work, building self-image, and developing creative opportunities. Students also began to identify content opportunities, determine key messages, develop content ideas according to audience characteristics, and recognize the importance of digital responsibility in the publication process.